2014
DOI: 10.1038/nature13850
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved magnetic field structure in the disk of a T Tauri star

Abstract: Magnetic fields in accretion disks play a dominant part during the star formation process but have hitherto been observationally poorly constrained. Field strengths have been inferred on T Tauri stars and possibly in the innermost part of their accretion disks, but the strength and morphology of the field in the bulk of a disk have not been observed. Spatially unresolved measurements of polarized emission (arising from elongated dust grains aligned perpendicularly to the field) imply average fields aligned wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
147
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(166 citation statements)
references
References 29 publications
15
147
1
Order By: Relevance
“…The MM1 upper limit is significantly lower than the typical values found in millimeter interferometric observations of dense cores around low and high mass star forming regions (∼2-10%, e.g. Girart et al 1999;Lai et al 2003;Girart et al 2006Girart et al , 2009Hull et al 2014;Zhang et al 2014), but it is not far from the values found in disks around lowmass young stellar objects (Hughes et al 2013;Rao et al 2014;Stephens et al 2014;Kataoka et al 2016). …”
Section: Observationsmentioning
confidence: 58%
“…The MM1 upper limit is significantly lower than the typical values found in millimeter interferometric observations of dense cores around low and high mass star forming regions (∼2-10%, e.g. Girart et al 1999;Lai et al 2003;Girart et al 2006Girart et al , 2009Hull et al 2014;Zhang et al 2014), but it is not far from the values found in disks around lowmass young stellar objects (Hughes et al 2013;Rao et al 2014;Stephens et al 2014;Kataoka et al 2016). …”
Section: Observationsmentioning
confidence: 58%
“…For example, there is no clear indication of a near-far side asymmetry in the polarized intensity of the HL Tau (Class I/II) disk from the CARMA observations at 1.3 mm (Stephens et al 2014), although the spatial resolution is rather limited. The lack of asymmetry is to be expected if the large grains are indeed settled to the mid-plane, as inferred from the shape of the gaps on the disk (Pinte et al 2016).…”
Section: Evolution Of Dust Settling From Polarization Of Inclined Disksmentioning
confidence: 99%
“…The polarization fraction for emission from aligned grains in the optically thin limit, p0, depends on many factors, including grain shape, composition and alignment efficiency. It can be quite high on parsec scales or larger (up to ∼ 20%; Planck Collaboration et al 2015), although the (sub)millimeter polarization fraction detected on the scale of protoplanetary disks is typically on the order of a few percent or less (e.g., Stephens et al 2014). For illustration purposes, we adopt p0 = 3% in Fig.…”
Section: Polarization From Direct Emissionmentioning
confidence: 99%
See 2 more Smart Citations